Ingestion of Microplastic Fibres, But Not Microplastic Beads, Impacts Growth Rates in the Tropical House Cricket Gryllodes Sigillatus - Fudlosid, Serita; Ritchie, Marshall W.; Muzzatti, Matthew J.; Allison, Jane E.; Provencher, Jennifer; MacMillan, Heath A. (Frontiers in Physiology, 2022)
Microplastic is a growing concern as an environmental contaminant as it is ubiquitous in our ecosystems. Microplastics are present in terrestrial environments, yet the majority of studies have focused on the adverse effects of microplastics on aquatic biota. We hypothesized that microplastic ingestion by a terrestrial insect would have localized effects on gut health and nutrient absorption, such that prolonged dietary microplastic exposure would impact growth rate and adult body size. We further hypothesized that plastic form (fibres vs. beads) would influence these effects because of the nature of gut-plastic interactions. Freshly hatched tropical house crickets (Gryllodes sigillatus) were fed a standard diet containing different concentrations of either fluorescent polyethylene microplastic beads (75-105 µm), or untreated polyethylene terephthalate microfibers (<5 mm) until they died or reached adulthood (approximately 8 weeks). Weight and body length were measured weekly and microplastic ingestion was confirmed through fluorescence microscopy and visual inspection of the frass. While, to our surprise, we found no effect of polyethylene beads ingestion on growth rate or final body size of G. sigillatus, females experienced a reduction in size and weight when fed high concentrations of polyethylene terephthalate microfibers. These results suggest that high concentrations of polyethylene beads of the 100 µm size range can pass through the cricket gut without a substantial negative effect on their growth and development time, but high concentrations of polyethylene terephthalate microfibers cannot. Although we report the negative effects of microplastic ingestion on the growth of G. sigillatus, it remains uncertain what threats microplastics pose to terrestrial insects.